2020
DOI: 10.37201/req/030.2020
|View full text |Cite
|
Sign up to set email alerts
|

Is the universal population Hepatitis C virus screening a cost-effective strategy? A systematic review of the economic evidence

Abstract: Background. Efficient strategies are needed in order to achieve the objective of the WHO of eradicating Hepatitis C virus (HCV). Hepatitis C infection can be eliminated by a combination of direct acting antiviral (DAA). The problem is that many individuals remain undiagnosed. The objective is to conduct a systematic review of the evidence on economic evaluations that analyze the screening of HCV followed by treatment with DAAs. Methods. Eleven databases were performed in a 2015-2018-systematic review. Inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Screening for HCV, HBV, and HIV infections raises the awareness of healthcare professionals working in the surgical departments, ensures that the surgical procedure is reviewed, and allows more intensive infection control measures (such as face shield-visor, double gloves) (20,21). Preoperative screening is thought to be cost-effective in countries with high HCV and HBV seroprevalence (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Screening for HCV, HBV, and HIV infections raises the awareness of healthcare professionals working in the surgical departments, ensures that the surgical procedure is reviewed, and allows more intensive infection control measures (such as face shield-visor, double gloves) (20,21). Preoperative screening is thought to be cost-effective in countries with high HCV and HBV seroprevalence (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that confirmed the cost-effectiveness of the DAA treatments for HCV-infected patients were published in other countries [ 14 ]. Besides, previous studies have also revealed the favorable cost-effectiveness of DAA treatment for the patients regardless of their genotype [ 15 ], adolescent patients [ 16 ], patients with HIV infection [ 17 ], and the universal screening program for HCV followed by DAAs treatments for the general population and subpopulations including prisoners and injecting drug users [ 18 ]. These results led to the recommendations by the AASLD and EASL and should guide the judgments of the health policymakers.…”
Section: Introductionmentioning
confidence: 99%
“… 6 According to the Spanish Ministry of Health HCV Infection Screening Guide and the Observatory of Drugs and Addictions, in 2018 around 30% of the PWUD population infected with HCV was not aware of their status, 3 7 making screening and treatment programmes crucial. 8 Population-specific models need to be developed and implemented to simplify and facilitate access to testing, treatment and prevention services for marginalised groups such as PWUD. These models will also allow for taking advantage of synergies between healthcare services and other organisations addressing substance use.…”
Section: Introductionmentioning
confidence: 99%
“… 9 10 Furthermore, because the ‘test and treat’ strategy is cost-effective for HCV screening and because HCV can be easily cured with direct-acting antivirals (DAAs), the long-term consequences and spread of the disease can be prevented, making it possible to achieve the WHO global HCV elimination goal by 2030. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation